An in vitro investigation on the cytotoxic and nuclear receptor transcriptional activity of the mycotoxins fumonisin B1 and beauvericin. (22nd August 2016) - Fernández-Blanco, Celia; Frizzell, Caroline; Shannon, Maeve; Ruiz, Maria-Jose; Connolly, Lisa
Highlights: We investigate beauvericin and fumonisin B1 for endocrine disrupting activity. Beauvericin antagonised transcriptional activation of the progestagen and glucocorticoid receptors. Fumonisin B1 antagonised transcriptional activation of the androgen receptor. High Content Analysis is a powerful bio-analytical tool for the detection of pre-lethal toxicity. Abstract: Fumonisin B1 (FB1) and beauvericin (BEA) are secondary metabolites of filamentous fungi, which under appropriate temperature and humidity conditions may develop on various foods and feeds. To date few studies have been performed to evaluate the toxicological and endocrine disrupting effects of FB1 and BEA. The present study makes use of various in vitro bioassays including; oestrogen, androgen, progestagen and glucocorticoid reporter gene assays (RGAs) for the study of nuclear receptor transcriptional activity, the thiazolyl blue tetrazolium bromide (MTT) assay to monitor cytotoxicity and high content analysis (HCA) for the detection of pre-lethal toxicity in the RGA and Caco-2 human colon adenocarcinoma cells. At the receptor level, 0.001–10 μM BEA or FB1 did not induce any agonist responses in the RGAs. However at non-cytotoxic concentrations, an antagonistic effect was exhibited by FB1 on the androgen nuclear receptor transcriptional activity at 10 μM and BEA on the progestagen and glucocorticoid receptors at 1 μM. MTT analysis showed no decrease in cell viability at any concentration of FB1, whereas BEA showed a significant decrease in viability at 10 μM. HCA analysis confirmed that the reduction in the progestagen receptor transcriptional activity at 1 μM BEA was not due to pre-lethal toxicity. In addition, BEA (10 μM) induced significant toxicity in both the TM-Luc (progestagen responsive) and Caco-2 cells.